Advances in metabolic reprogramming of renal tubular epithelial cells in sepsis-associated acute kidney injury - Wang, Tiantian; Huang, Ying; Zhang, Xiaobei; Zhang, Yi; Zhang, Xiangcheng (Frontiers in Physiology, 2024)
Sepsis-associated acute kidney injury presents as a critical condition characterized by prolonged hospital stays, elevated mortality rates, and an increased likelihood of transition to chronic kidney disease. sepsis-associated acute kidney injury suppresses fatty acid oxidation and oxidative phosphorylation in the mitochondria of renal tubular epithelial cells, thus favoring a metabolic shift towards glycolysis for energy production. This shift acts as a protective mechanism for the kidneys. However, an extended reliance on glycolysis may contribute to tubular atrophy, fibrosis, and subsequent chronic kidney disease progression.prospective strategies to counteract sepsis-associated acute kidney injury by restoring normal metabolic function, offering potential therapeutic and preventive modalities. This review delves into the metabolic alterations of tubular epithelial cells associated with sepsis-associated acute kidney injury, stressing the importance of metabolic reprogramming for the immune response and the urgency of metabolic normalization.We present various intervention targets that could facilitate the recovery of oxidative phosphorylation-centric metabolism. These novel insights and strategies aim to transform the clinical prevention and treatment landscape of sepsis-associated acute kidney injury, with a focus on metabolic mechanisms. This investigation could provide valuable insights for clinicians aiming to enhance patient outcomes in the context of sepsisassociated acute kidney injury.